MANFAAT HASIL BELAJAR DESAIN KOSTUM KREASI SEBAGAI KESIAPAN MENJADI COSTUME DESIGNER - Bella Hikmah Melati; Pipin Tresna P (Fesyen Perspektif, 2016)
Fashion would not only serves as a body covering , but fashion can also be a medium of entertainment and media promotion. Carnival fashion is one of fashion show demonstrating costumes creation that unique and interesting. To design costumes unique creation and aesthetic is it takes costume designers. Costume desaigner is a designer who designed fashion special used in special occasions as parade fashion, carnival fashion and costume party. Knowledge and skills to be costume designer can be learned in learning design costumes creation in lecture design projects vogue in course of study of fashion PKK FPTK UPI. The purpose of this research is to obtain data benefits of study result of the costume design creation as readiness become costume designers. Methods used in this research is a method of descriptive with an instrument shaped gatherer poll data. he population in this research is a student of education fashion choice management package design fashion 2012-2013. The results of the study showed that of learning design costumes creation the majority of respondents know of the benefits of study results design costumes creation as readiness be costume designer. The results of research is expected can be used as the information and additional knowledge of knowledge within the fashion management section especially in developing knowledge and skill in designing costumes creation , making costumes creation in accordance with the characteristics of a costume which is raised and can dig the potential that exists on a student.